2023
DOI: 10.1371/journal.pone.0286406
|View full text |Cite
|
Sign up to set email alerts
|

A hyperlocal hybrid data fusion near-road PM2.5 and NO2 annual risk and environmental justice assessment across the United States

Abstract: Exposure to traffic-related air pollutants (TRAPs) has been associated with numerous adverse health effects. TRAP concentrations are highest meters away from major roads, and disproportionately affect minority (i.e., non-white) populations often considered the most vulnerable to TRAP exposure. To demonstrate an improved assessment of on-road emissions and to quantify exposure inequity in this population, we develop and apply a hybrid data fusion approach that utilizes the combined strength of air quality obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…31−33 National and multicity studies of pollution disparities demonstrate that certain minoritized groups tend to be affected more than others, particularly people identifying as Black and African American, Hispanic or Latino, Asian and Asian American, and American Indian and Alaska Native. 19,34,35 Studies of individual cities demonstrate similar results. 18,36,37 Large-scale studies that report national or multicity averages often discuss the range of values for pollution disparities between the cities as being quite large but lack deeper insight into this phenomenon.…”
Section: ■ Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…31−33 National and multicity studies of pollution disparities demonstrate that certain minoritized groups tend to be affected more than others, particularly people identifying as Black and African American, Hispanic or Latino, Asian and Asian American, and American Indian and Alaska Native. 19,34,35 Studies of individual cities demonstrate similar results. 18,36,37 Large-scale studies that report national or multicity averages often discuss the range of values for pollution disparities between the cities as being quite large but lack deeper insight into this phenomenon.…”
Section: ■ Introductionmentioning
confidence: 65%
“…National and multicity studies of pollution disparities demonstrate that certain minoritized groups tend to be affected more than others, particularly people identifying as Black and African American, Hispanic or Latino, Asian and Asian American, and American Indian and Alaska Native. ,, Studies of individual cities demonstrate similar results. ,, Large-scale studies that report national or multicity averages often discuss the range of values for pollution disparities between the cities as being quite large but lack deeper insight into this phenomenon. Sociology researchers have also identified this disparity in disparities and have attributed it to the settlement patterns and urban development of individual cities, noting that residential segregation could increase or decrease a racial or ethnic group’s proximity to an environmental hazard .…”
Section: Introductionmentioning
confidence: 99%
“…Bramble et al [ 34 ] showed that higher exposures to multiple air pollutants and cumulative effects are disproportionately impacting historically marginalized communities, i.e., UFPM are higher than average for Black, 15%; Hispanic, 6%; Native American, 8%; and Pacific Islanders 11%. Valencia et al [ 35 ] estimated that minorities within 100 m from major roads are exposed to up to 15% more PM 2.5 and up to 35% more NO 2 than their white counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Previous CTM downscaling approaches have been conducted by running a full CTM simulation and then running local scale dispersion models for a certain sector. 13,31,32 This approach is computationally demanding and requires major meteorological and terrain assumptions, as well as a simplified representation of the relevant chemical processes (i.e., assumptions regarding the conversion of NO x emissions to NO 2 ). These local factors begin to have a large impact for high-resolution modeling.…”
Section: Theoretical Basismentioning
confidence: 99%